Are sugars-free medicines more erosive than sugars-containing medicines? An in vitro study of paediatric medicines with prolonged oral clearance used regularly and long-term by children - ANNE MAGUIRE, WASIM BAQIR, & JUNE HEATHER NUNN (IAPD and Blackwell, 2007)
The reduced use of sugars-containing (SC) liquid medicines has increased the use of other dose forms, potentially resulting in more widespread dental effects, including tooth wear. The aim of this study was to assess the erosive potential of 97 paediatric medicines in vitro.